2019
DOI: 10.1039/c8ra10186h
|View full text |Cite
|
Sign up to set email alerts
|

A general route to modify diatomite with niobates for versatile applications of heavy metal removal

Abstract: A general solution-phase strategy is developed to synthesize nanostructure niobates such as MnNb 2 O 6 , SnNb 2 O 6 and ZnNb 2 O 6 on natural mineral diatomite for water environmental remediation. (NH 4 ) 2 C 2 O 4 aqueous solution is the key to achieve a scalable and controllable synthesis of niobate/diatomite hybrid systems, which generates NH 3 $H 2 O for surface etching activation of diatomite, and H 2 C 2 O 4 for complexation dissolution of Nb 2 O 5 , enabling the heterogeneous crystallization process to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Based on the characteristics of diatomite, our research group has developed a series of diatomite-based composites, broadening their applications in sewage purification. Employing a universal synthesis approach, the solution-phase route was developed by Wu et al (2019) to synthesize nanostructured niobates on natural mineral diatomite (figures 10(a)-(c)) [141]. Interestingly, the system of niobates@diatomite can be adjusted using for the photoreduction of Cr(VI) to Cr(III), the physical eliminating Fe(III), and the direct chemisorption of Pb(II).…”
Section: Diatomite As a Carrier For Composited Materialsmentioning
confidence: 99%
“…Based on the characteristics of diatomite, our research group has developed a series of diatomite-based composites, broadening their applications in sewage purification. Employing a universal synthesis approach, the solution-phase route was developed by Wu et al (2019) to synthesize nanostructured niobates on natural mineral diatomite (figures 10(a)-(c)) [141]. Interestingly, the system of niobates@diatomite can be adjusted using for the photoreduction of Cr(VI) to Cr(III), the physical eliminating Fe(III), and the direct chemisorption of Pb(II).…”
Section: Diatomite As a Carrier For Composited Materialsmentioning
confidence: 99%
“…Wang, Yang et al modified the diatomite by easy alkaline treatment. The crude diatomite was dispersed in NaOH solution at 90 °C while stirring for 2 h. After separation, the modified diatomite was washed several times with water and anhydrous ethanol until a pH value close to neutral was obtained 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The next step was drying at room temperature to an air-dry state. Thermal activation was carried out by annealing the native, pre-washed and sieved diatomite in a muffle furnace for 3 h at 440–460°C 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, extensive studies have been reported to unravel the scopeo fs uch functional materials as activated porous carbon, [5] zeolites, [6] silica particles, [7][8][9][10][11][12][13] graphene oxide, [14,15] metals or metal oxides, [16,17] natural minerals [18][19][20] etc. as adsorbents for remediationo fm etal ions from water.T he search for new and efficient adsorbentsh as prompted the design and synthesis of functional polymers, [21][22][23][24][25][26][27] metal organic frameworks, [28][29][30] polymeric composites [31][32][33] and biohybrids.…”
Section: Introductionmentioning
confidence: 99%